Demographic Indicators in The Republic of Uzbekistan and Their Importance in Medicine - Khasanova Shoirakhon Abdujabborovna (Zien Journals, 2023)
Demography is a science that deals with the laws of the renewal of the population. It studies the laws of birth, death, marriage and annulment of marriage, renewal of spouses and families, as a unit of these processes, the laws of the renewal of the population as a whole and their dependence on social causes. will try; it studies the age and gender composition of the population, marriage-related and family changes, and their interrelationship with demographic processes. It describes the number and density of the population, the ratio of the urban population to the rural population, religious beliefs, migration, as well as the dependence of these processes on economic and social indicators: income and employment level, education level, race and ethnicity.
Keywords: Demography; health; medicine; method